Effect of the application of polluted wheat (Triticum aestivum L. Thell.) straw during plowing on the transfer of radiocesium from the soil to komatsuna (Brassica rapa L. var. perviridis). Issue 2 (3rd March 2016) - Nihei, Naoto; Fujimura, Shigeto; Tanoi, Keitaro; Yamashita, Nobuo; Morimoto, Sho; Nakanishi, Tomoko M.; Murakami, Toshihumi
ABSTRACT: Radioactive substances were released into the environment after the nuclear accident at the Fukushima Daiichi Nuclear Power Station; this led to the contamination of the soil at Fukushima Prefecture. Mixing of organic matter with soil during plowing is known to influence radiocesium ( 134 Cs and 137 Cs) absorption by crops. However, the effect of mixing organic matter polluted by radioactive substances during plowing on radiocesium absorption by plants is not yet known. The aim of this study was to investigate the effect on the radiocesium absorption by komatsuna ( Brassica rapa L. var. perviridis ) cultivated in a 45-L container containing Andosol (14, 300 Bq kg −1 ) or Gray Lowland soil (33, 500 Bq kg −1 ) mixed with polluted wheat ( Triticum aestivum L. Thell.) straw (2080 Bq kg −1 ). The radiocesium concentration of the plants and the soil and the amount of exchangeable radiocesium in the soil were determined using a germanium semiconductor. The transfer of radiocesium from the soil to plants decreased by 53 and 27% in Andosol and Gray Lowland soil, respectively, after the application of 10 t ha −1 polluted wheat straw. This reduction in the level of radiocesium transfer might be attributed to potassium contained in the wheat straw, which might compete with cesium during membrane transport and thereby block the transport of cesium from the soil solution to the roots and from the roots to the shoots. Alternatively, the applied wheat straw probably absorbed radiocesium and decreased the amount of exchangeable radiocesium in the soil. Our findings suggest that the mixing of polluted wheat straw with contaminated soil might influence the absorption of radiocesium content by agricultural products. Further studies are warranted to determine the long-term effects of the application of polluted wheat straw on the rate of radiocesium transfer to crops.